Study the optimal conditions for the preparation of hydroxyapatite in the three-component system: Ca (NO3)2- (NH4)2HPO4- NH3.H2O to be used medically - غنام , نزار; خليل , علي; أسعد , منذر (Latakia University Journal -Basic Sciences Series, 2022)
The aim of this research is to study the optimal conditions for the preparation of hydroxyapatite , Chemical formula: Ca10(PO4)6(OH)2 (HA). In the three-component system: Ca(NO3)2-(NH4)2HPO4-NH3.H2O , Calcium Nitrate was prepared based on the calcification of the white eggshell . to obtain calcium oxide (CaO), which is treated with nitrogen acid, while ammonium phosphate Mono hydrogen and ammonium solution was taken from its pure packaging. Hydroxyapatite (HA) Ca10 (PO4) 6 (OH)2was prepared under specific conditions, mainly: concentration of solutions used, speed of addition of reagents, reaction mix temperature, rotational speed, purity of materials used, and pH of the solution. The study showed that the solid compound recorded in the three-component system, which was separated from the liquid phase and dried and chemically analyzed, has the total chemical formula Ca10 (PO4) 6 (OH)2 and has a Molar ratio of Ca / P= 1.666 . and the preparation process was better in the model burned from the dried model and confirmed by the study of samples of the models dried and burned by IR infrared spectroscopy and XRD X ray diffraction spectroscopy, The burner model was a crystalline product, but in the dried model the output was mixed crystalline and not crystalline.